2017
DOI: 10.1038/s41598-017-15717-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration combined with size exclusion chromatography efficiently isolates extracellular vesicles from cell culture media for compositional and functional studies

Abstract: Appropriate isolation methods are essential for unravelling the relative contribution of extracellular vesicles (EVs) and the EV-free secretome to homeostasis and disease. We hypothesized that ultrafiltration followed by size exclusion chromatography (UF-SEC) provides well-matched concentrates of EVs and free secreted molecules for proteomic and functional studies. Conditioned media of BEAS-2B bronchial epithelial cells were concentrated on 10 kDa centrifuge filters, followed by separation of EVs and free prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
174
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 233 publications
(197 citation statements)
references
References 26 publications
8
174
0
1
Order By: Relevance
“…Benedikter et al (2017) found that EV from CSEstimulated pulmonary epithelial cells did not significantly modify IL-8 secretion by naïve cells. The same CSE-EV were less potent inducers of monocyte adhesion to endothelial cells than EV secreted by unexposed cells , questioning a role of CSE-induced EV in immune cell recruitment.…”
Section: Conflicting Datamentioning
confidence: 83%
“…Benedikter et al (2017) found that EV from CSEstimulated pulmonary epithelial cells did not significantly modify IL-8 secretion by naïve cells. The same CSE-EV were less potent inducers of monocyte adhesion to endothelial cells than EV secreted by unexposed cells , questioning a role of CSE-induced EV in immune cell recruitment.…”
Section: Conflicting Datamentioning
confidence: 83%
“…Therefore, we filtered the supernatant through a 0.22 μm filter to remove larger particles. Recently it was reported that ultrafiltration, rather than ultracentrifugation, results in less damage to vesicles and a higher recovery rate 24 . While most ultrafiltration substrates will bind EVs, regenerated cellulose does not 25 , so we decanted and concentrated the 0.22 μm filtrate using a 10 kD mwco regenerated cellulose filter to the final volume of 1 ml at 4C (MilliporeSigma, Burlington MA, USA; Cat # UFC901008) (FIG 1B).…”
Section: Fractionationmentioning
confidence: 99%
“…EV isolation was performed by a combination of 10 kDa ultrafiltration and sepharose CL-4B SEC as described previously [13]. In brief, 60 ml of conditioned media were concentrated to 500 μl on an Amicon Ultra-15 Centrifugal Filter Unit with Ultracel 10 membrane (10 kDa MWCO, Merck Millipore), followed by separation of EVs and free protein by SEC on a 10 ml sepharose CL4B column into 24 fractions of 0.5 ml.…”
Section: Ev Isolationmentioning
confidence: 99%
“…Although the airway epithelium forms the first line of contact with inhaled cigarette smoke, studies on the functions of EVs released by smoke-exposed airway epithelial cells are scarce. Previously, we have shown that airway epithelial cells secrete small EVs (mode size 110 nm) expressing the tetraspanins CD63, CD81 and CD9, at control conditions and when exposed to CSE [5,13]. In this study, we aimed to predict the functions of these EVs.…”
Section: Introductionmentioning
confidence: 99%